Task Sharing and Task Shifting (TSTS) in the Management of Africans with Hypertension: A Call For Action-Possibilities and Its Challenges - Oluseyi Ademola Adejumo; Reuben Mutagaywa; Florence Koryo Akumiah; Adeseye Abiodun Akintunde (Ubiquity Press, 2024)
Hypertension is a leading cause of mortality globally and one of the most common risk factors for cardiovascular disease. Diagnosis, awareness, and optimal treatment rates are suboptimal, especially in low- and middle-income countries, with attendant high health consequences and grave socioeconomic impact. There is an enormous gap between disease burden and physician-patient ratios that needs to be bridged. Task sharing and task shifting (TSTS) provide a viable temporary solution. However, sociocultural, demographic, and economic factors influence the effective uptake of such interventions. This review discusses the dynamics of TSTS in the African context looking at challenges, feasibility, and approach to adopt it in the management of hypertension in Africa.